Inclusion of green fodder sorghum in the diet of lactating buffalo cows: influence on milk yield and composition, and economic sustainability - Capezzuto, Francesco; Infascelli, Lorenzo; Iommelli, Piera; Franco, Francesco; Infascelli, Federico; Tudisco, Raffaella (Frontiers in Veterinary Science, 2026)
IntroductionEffects on production performance from dietary inclusion of green fodder Sorghum in lactating water buffalos were explored. Rising feed price volatility makes low-cost forage crops a strategic option to reduce dairy farming costs. The use of green fodder sorghum through the cut-and-carry system improves forage utilization, nutrient intake, and milk yield and composition.MethodsA total of 40 buffaloes, homogeneous in terms of milk yield, parity and body condition score (BCS), were selected and assigned to two groups: control group (C) and treated group (S). Experimental diets were offered to cover requirements as a Total Mixed Ration (TMR) with the inclusion of green fodder Sorghum (treated group, at an amount of 14.7% of TMR) and without (control group). The trial was conducted from July to September 2024. Milk samples were collected and analysed for chemical composition somatic cell count and urea. In addition, feed and faecal samples were collected to determine chemical composition and digestibility.ResultsThe inclusion of green fodder sorghum did not affect milk yield (C: 10.4 kg/head/d vs. S: 10.4 kg/head/d) or milk composition, with the exception of fat content, which was significantly higher in the treated group (C: 71.2 g/kg vs. S: 85.0 g/kg; p < 0.01). This increase was associated with improved digestibility of NDF and ADF of the experimental diet compared to the control diet (p < 0.01).DiscussionThe economic assessment revealed that partially replacing corn silage and other dietary ingredients with green sorghum should reduce feeding costs by 0.27 EUR/head/day, making this strategy economically advantageous. Overall, the inclusion of green fodder sorghum proved beneficial in terms of cost efficiency and productive performance, aligning with the sustainability goals of the 2030 Agenda, particularly SDGs 12 and 13.